2022
DOI: 10.1093/jhered/esac005
|View full text |Cite
|
Sign up to set email alerts
|

Avian Introgression Patterns are Consistent With Haldane’s Rule

Abstract: According to Haldane’s Rule, the heterogametic sex will show the greatest fitness reduction in a hybrid cross. In birds, where sex is determined by a ZW-system, female hybrids are expected to experience lower fitness compared to male hybrids. This pattern has indeed been observed in several bird groups, but it is unknown whether the generality of Haldane’s Rule also extends to the molecular level. First, given the lower fitness of female hybrids, we can expect maternally inherited loci (i.e. mitochondrial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…) then barrier loci, both recessive and dominant, may accumulate faster. Reduced gene flow on the Brenthis Z chromosome mirrors findings in other butterfly systems (Xiong et al 2022;Rosser et al 2022), as well as in birds (Irwin 2018;Ottenburghs 2022), suggesting that Z chromosomes often accumulate reproductive isolation at a faster rate than autosomes. Given that there are likely many barriers to gene flow between B. daphne and B. ino, especially on the Z, it may be inaccurate to describe the history of these species as 'chromosomal speciation'.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…) then barrier loci, both recessive and dominant, may accumulate faster. Reduced gene flow on the Brenthis Z chromosome mirrors findings in other butterfly systems (Xiong et al 2022;Rosser et al 2022), as well as in birds (Irwin 2018;Ottenburghs 2022), suggesting that Z chromosomes often accumulate reproductive isolation at a faster rate than autosomes. Given that there are likely many barriers to gene flow between B. daphne and B. ino, especially on the Z, it may be inaccurate to describe the history of these species as 'chromosomal speciation'.…”
mentioning
confidence: 55%
“…2022; Rosser et al . 2022), as well as in birds (Irwin 2018; Ottenburghs 2022), suggesting that Z chromosomes often accumulate reproductive isolation at a faster rate than autosomes. Given that there are likely many barriers to gene flow between B. daphne and B. ino , especially on the Z, it may be inaccurate to describe the history of these species as ‘chromosomal speciation’.…”
Section: Discussionmentioning
confidence: 99%
“…The four bipartitions at the base of the core bird-of-paradise radiation (excluding Parotia ) have the lowest wCF and sCF scores across the phylogeny ( Figure S7 B); they coincide with strong incongruence between Z/A topologies and the frequency of competing topologies remains relatively stable along the 10 macrochromosomes. Variation in the tempo and mode of differentiation between Z/A is common in birds 42 and both the “fast-Z” and “large-Z” effect are often invoked as possible explanations. However, elevated differentiation on the Z chromosome is not necessarily driven by “adaptation” or “reproductive isolation,” and can also be the outcome of accelerated drift due to low Ne.…”
Section: Resultsmentioning
confidence: 99%
“…According to Haldane's rule, hybrid female birds are expected to have less fitness than hybrid males. A meta‐analysis of 30 studies testing Haldane's rule in avian species revealed that 90% adhered to the rule (Ottenburghs 2022). When studying captive waterfowl, Kirby et al (2004) observed that most (65–66%) of the F 1 hybrid offspring of American black ducks and mallards were male.…”
Section: Discussionmentioning
confidence: 99%